Exploring mothers’ perceptions of the role of integrated health posts (Posyandu) in stunting prevention: A qualitative study - Ikasari, Filia Sofiani; Pusparina, Iis (Lentera Perawat, 2026)
Background: Stunting remains a public health problem with long-term consequences for child growth and development. Integrated Health Posts (Posyandu) play a strategic role as community-based health services in stunting prevention; however, their utilization is influenced by mothers’ perceptions of the role and function of Posyandu. Objective: This study aimed to gain an in-depth understanding of mothers’ perceptions of the role of Posyandu in stunting prevention in the working area of Martapura 1 Primary Health Center. Methods: This study employed a qualitative design with a descriptive phenomenological approach. The study was conducted in June 2025 in the working area of Martapura 1 Primary Health Center. Participants were recruited using purposive sampling, with inclusion criteria of mothers who had stunted children under five years of age. A total of 13 participants were involved until data saturation was achieved. Data were collected through in-depth interviews using semi-structured interview guidelines and analyzed through transcription, coding, categorization, and thematic analysis with the assistance of NVivo 12 software. Results: The findings identified four themes related to mothers’ perceptions of the role of Posyandu in stunting prevention in the working area of Martapura 1 Primary Health Center: (1) visit patterns; (2) Posyandu services; (3) perceived benefits of Posyandu; and (4) mothers’ expectations. Conclusion: Mothers primarily perceived Posyandu as a place for routine child growth monitoring, while its role in stunting prevention was not fully understood. These findings indicate a gap between the ideal role of Posyandu in stunting prevention and mothers’ perceptions at the community level.